An exploration of how U.S. Army officers attending the U.S. Army Command and General Staff College decide whether or not to attend graduate school: a qualitative case study - Vance, Charles David (Kansas State University, 2013)
This qualitative case study explored how U.S. Army Command and General Staff College (CGSC) students decided whether or not to attend graduate school. The focus was on how U.S. Army students made their decision. The purpose of the study was to illuminate the issues related to this decision in adult development, adult learning, career decision making, and participation in adult learning activities. These issues were explored using the students’ own words during their interviews in which they described how they made their respective decisions. This research analyzed interviews with 26 students, 12 who either decided to attend one of the graduate programs available to CGSC students or were already in a master’s degree program, and 14 who elected not to attend any of the graduate programs offered. The analysis explored how U.S. Army CGSC students made their decision about graduate school, the process used in making their respective decisions, and the factors that influenced their decisions. Analysis of the students’ interviews answered the primary research question and the four subordinate research questions. Not surprisingly, all the students indicated that military career requirements, post-military career aspirations and requirements, family considerations, and previous academic experience influenced their decision whether or not to attend graduate school. The extent to which their decision was influenced varied, but everyone interviewed expressed some degree of influence of those factors. Not expected were the common themes that emerged from analysis of the interview transcripts of CGSC students. Those themes centered around self-efficacy and confidence, goal setting and achievement, persistence, time management, life issues, guidance and mentorship, perceived quality of the degree or value, and the CGSC master’s program (Master of Military Art and Science).
Keywords: Master's degree; Graduate school; Command and General Staff College; Decision making; Adult education; Adult Education (0516)